Investigation of Lipoproteins Oxidation Mechanisms by the Analysis of Lipid Hydroperoxide Isomers - Shunji Kato; Yusuke Osuka; Saoussane Khalifa; Takashi Obama; Hiroyuki Itabe; Kiyotaka Nakagawa (MDPI AG, 2021)
The continuous formation and accumulation of oxidized lipids (e.g., lipid hydroperoxides (LOOH)) which are present even in plasma lipoproteins of healthy subjects, are ultimately considered to be linked to various diseases. Because lipid peroxidation mechanisms (i.e., radical, singlet oxygen, and enzymatic oxidation) can be suppressed by certain proper antioxidants (e.g., radical oxidation is efficiently suppressed by tocopherol), in order to suppress lipid peroxidation successfully, the determination of the peroxidation mechanism involved in the formation of LOOH is deemed crucial. In this study, to determine the peroxidation mechanisms of plasma lipoproteins of healthy subjects, we develop novel analytical methods using liquid chromatography-tandem mass spectrometry (LC-MS/MS) for 1-palmitoyl-2-linoleoyl-sn-glycero-3-phosphocholine hydroperoxide (PC 16:0/18:2;OOH) and cholesteryl linoleate hydroperoxide (CE 18:2;OOH) isomers. Using the newly developed methods, these PC 16:0/18:2;OOH and CE 18:2;OOH isomers in the low-density lipoprotein (LDL) and high-density lipoprotein (HDL) of healthy subjects are analyzed. Consequently, it is found that predominant PC 16:0/18:2;OOH and CE 18:2;OOH isomers in LDL and HDL are PC 16:0/18:2;9OOH, PC 16:0/18:2;13OOH, CE 18:2;9OOH, and CE 18:2;13OOH, which means that PC and CE in LDL and HDL are mainly oxidized by radical and/or enzymatic oxidation. In conclusion, the insights about the oxidation mechanisms shown in this study would be useful for a more effective suppression of oxidative stress in the human organism.